USP5 inhibits anti-RNA viral innate immunity by deconjugating K48-linked unanchored and K63-linked anchored ubiquitin on IRF3. - Zigang Qiao; Dapei Li; Fan Zhang; Jingfei Zhu; Siying Liu; Xue Bai; Haiping Yao; Zhengrong Chen; Yongdong Yan; Xiulong Xu; Feng Ma (PLoS Pathogens)
Interferon regulatory factor 3 (IRF3) is a central hub transcription factor that controls host antiviral innate immunity. The expression and function of IRF3 are tightly regulated by the post-translational modifications. However, it is unknown whether unanchored ubiquitination and deubiquitination of IRF3 involve modulating antiviral innate immunity against RNA viruses. Here, we find that USP5, a deubiquitinase (DUB) regulating unanchored polyubiquitin, is downregulated during host anti-RNA viral innate immunity in a type I interferon (IFN-I) receptor (IFNAR)-dependent manner. USP5 is further identified to inhibit IRF3-triggered antiviral immune responses through its DUB enzyme activity. K48-linked unanchored ubiquitin promotes IRF3-driven transcription of IFN-β and induction of IFN-stimulated genes (ISGs) in a dose-dependent manner. USP5 simultaneously removes both K48-linked unanchored and K63-linked anchored polyubiquitin chains on IRF3. Our study not only provides evidence that unanchored ubiquitin regulates anti-RNA viral innate immunity but also proposes a novel mechanism for DUB-controlled IRF3 activation, suggesting that USP5 is a potential target for the treatment of RNA viral infectious diseases.